A Selective Histamine H4 Receptor Antagonist, JNJ7777120, Is Protective in a Rat Model of Transient Cerebral Ischemia - Dettori, Ilaria; Gaviano, Lisa; Melani, Alessia; Lucarini, Laura; Durante, Mariaconcetta; Masini, Emanuela; Pedata, Felicita (Frontiers in Pharmacology, 2018)
Cerebral ischemia is a multifactorial pathology characterized by different events evolving in time. The acute injury, characterized by excitoxicity, is followed by a secondary brain injury that develops from hours to days after ischemia. Extracellular levels of histamine increase in the ischemic areas after focal cerebral ischemia induced by occlusion of the middle cerebral artery (MCAo). The histamine H4 receptor (H4R) is predominantly expressed in cell types of immune system where is involved in the regulation of immunological and inflammatory response, and in numerous areas of the Central Nervous System (CNS) including cortex and striatum. Our aim was to assess the putative neuroprotective effects of the potent and selective H4R antagonist, JNJ7777120 (JNJ), chronically administered (1 mg/kg, i.p., twice/day for 7 days) on damage parameters in a rat model of focal ischemia induced by transient MCAo (tMCAo). Chronic treatment with the H4R antagonist JNJ, significantly protected from the neurological deficit and from body weight loss after tMCAo. Seven days after the ischemic insult, JNJ reduced the volume of the ischemic cortical and striatal damage, the number of activated microglia and astrocytes in the ischemic cortex and striatum, and decreased the plasma levels of IL-1β and TNF-α, while increased the levels of IL-10. Two days after ischemia, JNJ has reduced granulocyte infiltration in the ischemic areas. Results demonstrate that the selective antagonist of H4R, JNJ, systemically and chronically administered after ischemia, reduces the ischemic brain damage, improves the neurological deficit and decreases blood pro-inflammatory cytokines, suggesting that H4R is a valuable pharmacological target after focal brain ischemia.